Comparative yield, cost and sensory characteristics of "lechon" using three roasting techniques - Bangsal, Armi J.; Perdigon, Grace P. (1983)
The main objective of this study was to compare the standard techniques of roasting "lechon" namely, conventional, open rotisserie and oven rotisserie methods on the basis of yield, cost and sensory characteristics. This was carried out first by developing standard procedures for the three roasting techniques. The criteria used to determine standard conditions were yield, cost and sensory characteristics. The parameters used for each method are as follows: conventional - 10, 14, 18 kg charcoal; open rotisserie - 8, 13, 18 rpm; and oven rotisserie - 10, 12, 14 kg charcoal. Three groups of 100-day old Large White hogs were used as raw materials for the first phase of this study. Each group consisted of nine dressed carcasses of about 25 kg each. The standard conditions established for each technique were: 18 kg and 14-16 rpm manual rotation for conventional; 18 kg and 8 rpm for open rotisserie, and 8 rpm with 14 kg charcoal for oven rotisserie. In the second phase, nine carcasses were also used to obtain necessary data on yield, cost and sensory characteristics to compare the three standardized roasting methods. The oven rotisserie method was found to require the least time for cooking "lechon". This method also gave the highest yield and the lowest cos. The "lechon" cooked in this method had the highest mean score in skin crispness and meat juiciness among the three roasting methods. There were no significant differences among the "lechon" attributes in the three methods of roasting except in the overall assessment. Furthermore, the t-test on the scores for overall assessment indicated a significant difference existed between conventional and oven rotisserie and between open and oven rotisserie at 5% and 1% level of significance, respectively. However, in the conventional and open rotisserie methods, no significant difference was noted.
Thesis (M.S. Foods and Nutrition)--University of the Philippines Diliman.
Keywords: Roasting (Cookery).